Feature-driven classification reveals potential comorbid subtypes within childhood apraxia of speech - Catherine M. Stein; Penelope Benchek; Gabrielle Miller; Noémi B. Hall; Dhanya Menon; Lisa Freebairn; Jessica Tag; Jennell Vick; H. Gerry Taylor; Barbara A. Lewis; Sudha K. Iyengar (BMC, 2020)
Abstract Background Childhood apraxia of speech (CAS) is a neurodevelopmental disorder with heterogeneous communication and other comorbid manifestations. While previous studies have characterized speech deficits associated with CAS, few studies have examined variability in reading and language and/or other developmental comorbidities. We sought to identify comorbid subgroups within CAS that could be clinically relevant as well as genetically distinctive. Methods In a group of 31 children with CAS and 8 controls, we performed hierarchical cluster analysis utilizing measures of articulation, vocabulary, and reading. We also conducted a chart review of the children with CAS to examine other clinical characteristics in these children and their association with subgroup membership. Results We identified 3 comorbid subgroups within CAS of varying severity. The high severity subgroup was characterized by poor reading and vocabulary, and the moderate severity subgroup by poor reading and non-word repetition but average vocabulary, compared to the mild severity subgroup. Subgroups were indistinguishable with respect to speech sound production, the hallmark of CAS, all demonstrating poor articulation. Children in the most severe subgroup were more likely to have early problems feeding (p = 0.036). Conclusions Children with CAS may potentially be classified into comorbidity groups based on performance on vocabulary and reading measures, providing additional insight into the heterogeneity within CAS with implications for educational interventions.